Membaca Sejarah Membaca Sejarah Konstitusi Indonesia Era Reformasi (studi pemakzulan Presiden Abdurrahman Wahid): Konstitusional Pemakzulan Presiden - Moch Nafi Maulana (Eastasouth Institute, 2023)
Indonesia after the 1998 reform, had various hopes raised for the creation of a conducive country according to the initial ideals, namely Pancasila. The emergence of the name KH. Abdurrahman Wahid as an alternative presidential candidate from the center axis gave new hope to everyone. he was elected president in 1999, but in 2001 Gus Dur was removed by members of the DPR on the grounds of violations of State Policy such as the cases of Bruneigate, Buloggate, the replacement of the chief of the Indonesian National Police, and the decree dissolving the DPR/MPR. This type of research is library research using a historical juridical approach and is descriptive analysis in nature. The results of this study indicate that the dismissal of Gus Dur as president is unconstitutional. several indicators underlying the unconstitutional background of Gus Dur's dismissal including the existence and legality of the formation of a special committee.